A compositional analysis of native and decellularized porcine nasal septum cartilage - Tluczynski, Katharina; Breiter, Roman (Xenotransplantation, 2022)
Objectives: Decellularization of porcine septum cartilage is necessary for its application as xenogenic replacement material. The aim of this study was to investigate spatial differences of structure and composition in the whole native and decellularized porcine nasal septum. Subsequently, the results shall be compared with studies of human nasal septum. Methods: Ten porcine nasal septa were divided into six regions from caudal to cephalic and four regions from dorsal to ventral to create a grid of 24 approximately equal segments. All segments of five septal cartilages were decellularized separately by a wet chemical multistep procedure. The segments were analyzed to determine quantitative amounts of total collagen, chondrocytes, and sulfated glycosaminoglycans (sGAG). Results: The distribution of cell number showed no significant differences between the individual regions. For the distribution of collagen and sGAG, no significant differences could be identified from caudal to cephalic, both in native and decellularized tissue. From dorsal to ventral, native and decellularized nasal septum showed significant differences between individual regions. In native septum, linear regression analysis indicated a decreasing collagen and an increasing sGAG content from dorsal to ventral. After decellularization, an increasing collagen and a decreasing sGAG content was detected. Conclusion: The results of this study showed slightly but significant differences in the distribution of collagen and sGAG from dorsal to ventral. From caudal to cephalic, no differences could be observed. Compared to human, nasal septum differences in cell, collagen, and sGAG content were detected. Despite this, human and porcine nasal septum showed similar distributions and a consistently inverse linearity of collagen and sGAG content. Nevertheless, the midcaudal and midcephalic regions showed the highest porosity and a high stability and thus offer the best conditions for the revitalization of porcine tissue by human cells.
CRIS-Team Scopus Importer:2022-09-30
Keywords: cartilage tissue engineering; decellularized cartilage; distribution; nasal septum; porcine septal cartilage